PENGARUH KOMPETENSI, DISIPLIN DAN PEMBERIAN TAMBAHAN PENGHASILAN PEGAWAI (TPP) TERHADAP KINERJA PEGAWAI PADA DINAS PERTANIAN DAN PANGAN KABUPATEN POLEWALI MANDAR - Syamsi Syamsi; Maryadi Maryadi; Asniwati Asniwati (Lembaga Penelitian, Publikasi dan Pengabdian Masyarakat ITB Nobel Indonesia, 2022)
This study aims to analyze the effect of competence, discipline and providing additional employee income partially and simultaneously on the performance of the employees of the Department of Agriculture and Food, Polewali Mandar Regency. The research used in this study is a quantitative research method. The population in this study were employees of the Department of Agriculture and Food of Polewali Mandar Regency, which opened 114 civil servants. Sampling of this study was carried out using the slovin technique with a significant standard of 10%. So that it can be seen that the sample used in this study were employees of the Agriculture and Food Office of Polewali Mandar Regency, totaling 53 respondents. The data collection technique was carried out through a questionnaire/questionnaire where each respondent's answer was assessed using a score according to a Likert scale. The results of this study indicate that the results of the F test or simultaneous testing indicate that the Fcount value is 26,164 and Ftable with a value of 2.79. So it shows that Fcount > Ftable with a significance of 0.000 < 0.05. These results indicate that competence, discipline and the provision of additional employee income simultaneously have a significant effect on the performance of the employees of the Department of Agriculture and Food, Polewali Mandar Regency. From this description, it is known that competence, discipline and the provision of additional employee income partially have a positive and significant effect on the performance of the employees of the Department of Agriculture and Food, Polewali Mandar Regency. Furthermore, the competence variable is the most dominant influencing variable with a beta value of 0.467.